The Lung Inflammation and Skeletal Muscle Wasting Induced by Subchronic Cigarette Smoke Exposure Are Not Altered by a High-Fat Diet in Mice - Hansen, Michelle J. (Public Library of Science, 2013)
Obesity and cigarette smoking independently constitute major preventable causes of morbidity and mortality and obesity is known to worsen lung inflammation in asthma. Paradoxically, higher body mass index (BMI) is associated with reduced mortality in smoking induced COPD whereas low BMI increases mortality risk. To date, no study has investigated the effect of a dietary-induced obesity and cigarette smoke exposure on the lung inflammation and loss of skeletal muscle mass in mice. Male BALB/c mice were exposed to 4 cigarettes/day, 6 days/week for 7 weeks, or sham handled. Mice consumed either standard laboratory chow (3.5 kcal/g, 12% fat) or a high fat diet (HFD, 4.3 kcal/g, 32% fat). Mice exposed to cigarette smoke for 7 weeks had significantly more inflammatory cells in the BALF (P<0.05) and the mRNA expression of pro-inflammatory cytokines and chemokines was significantly increased (P<0.05); HFD had no effect on these parameters. Sham- and smoke-exposed mice consuming the HFD were significantly heavier than chow fed animals (12 and 13%, respectively; P<0.05). Conversely, chow and HFD fed mice exposed to cigarette smoke weighed 16 and 15% less, respectively, compared to sham animals (P<0.05). The skeletal muscles (soleus, tibialis anterior and gastrocnemius) of cigarette smoke-exposed mice weighed significantly less than sham-exposed mice (P<0.05) and the HFD had no protective effect. For the first time we report that cigarette smoke exposure significantly decreased insulin-like growth factor-1 (IGF-1) mRNA expression in the gastrocnemius and tibialis anterior and IGF-1 protein in the gastrocnemius (P<0.05). We have also shown that cigarette smoke exposure reduced circulating IGF-1 levels. IL-6 mRNA expression was significantly elevated in all three skeletal muscles of chow fed smoke-exposed mice (P<0.05). In conclusion, these findings suggest that a down-regulation in local IGF-1 may be responsible for the loss of skeletal muscle mass following cigarette smoke exposure in mice.